The Impact of Argument Quality, Perceived Usefulness, and Ease of Use on Purchase Intentions: Evidence from Viral Marketing of Mobile Applications in Indonesia - Chabib Nashrulloh (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This study investigates how argument quality, perceived usefulness (PU), and perceived ease of use (PEU) shape user attitudes (ATT) and purchase intentions (PI) toward mobile applications promoted through viral marketing. Using a quantitative survey of 200 Indonesian social‑media users, data were analysed with partial least squares‑structural equation modelling (SmartPLS 4). Results show that argument quality positively influences PU (β = 0.412; p < 0.001) and PEU (β = 0.346; p < 0.001). PU (β = 0.364; p < 0.001) and PEU (β = 0.233; p < 0.01) both enhance ATT, which in turn strongly predicts PI (β = 0.678; p < 0.001). The findings highlight the importance of rational, credible messaging and intuitive interface design in converting viral exposure into buying decisions.